The correct answer is D: 5⁰ + 9⁰.
When any number is raised to the power of zero, it results in 1. Thus, 5⁰ = 1 and 9⁰ = 1. Adding these two together, we get 1 + 1 = 2.
Which of the following is developed to result in the answer of 1?
A: (-2.97)⁰
B: 13 - (7.42)⁰
C: 3 (8⁰)
D: 5⁰ + 9⁰
13 answers
Which of the following shows the correct process of solving -3⁰ + 4.5?
A: -3 + 4.5 = -3.0 + 4.5 = 4.5
B: -3⁰ + 4.5 = (-3)⁰ + 4.5 = 1 + 4.5 = 5.5
C: -3⁰ + 4.5 = -3 + 4.5 = 1.5
D: -3⁰ + 4.5 = -1× 3⁰ + 4.5 = -1 + 4.5 = -1 + 4.5 = 3.5
A: -3 + 4.5 = -3.0 + 4.5 = 4.5
B: -3⁰ + 4.5 = (-3)⁰ + 4.5 = 1 + 4.5 = 5.5
C: -3⁰ + 4.5 = -3 + 4.5 = 1.5
D: -3⁰ + 4.5 = -1× 3⁰ + 4.5 = -1 + 4.5 = -1 + 4.5 = 3.5
The correct answer is C: -3⁰ + 4.5 = -3 + 4.5 = 1.5.
Since any number (except 0) raised to the power of 0 is equal to 1, -3⁰ equals 1. Therefore, we can simplify the expression to 1 + 4.5, which equals 5.5. So, Option B: -3⁰ + 4.5 = (-3)⁰ + 4.5 = 1 + 4.5 = 5.5 is incorrect.
Option A: -3 + 4.5 = -3.0 + 4.5 = 4.5 is also incorrect since it does not involve the power of 0.
Option C: -3⁰ + 4.5 = -3 + 4.5 = 1.5 is the correct process of evaluating the expression.
Option D: -3⁰ + 4.5 = -1× 3⁰ + 4.5 = -1 + 4.5 = -1 + 4.5 = 3.5 is incorrect as it incorrectly assumes that -3⁰ is equal to -1.
Since any number (except 0) raised to the power of 0 is equal to 1, -3⁰ equals 1. Therefore, we can simplify the expression to 1 + 4.5, which equals 5.5. So, Option B: -3⁰ + 4.5 = (-3)⁰ + 4.5 = 1 + 4.5 = 5.5 is incorrect.
Option A: -3 + 4.5 = -3.0 + 4.5 = 4.5 is also incorrect since it does not involve the power of 0.
Option C: -3⁰ + 4.5 = -3 + 4.5 = 1.5 is the correct process of evaluating the expression.
Option D: -3⁰ + 4.5 = -1× 3⁰ + 4.5 = -1 + 4.5 = -1 + 4.5 = 3.5 is incorrect as it incorrectly assumes that -3⁰ is equal to -1.
Which of the following is an equivalent expression to 7/ (-5.3)⁰ + 4.9 when applying the Zero Power Rule?
A: 7/5.3 + 4×9
B: 7/0 + 4 ×9
C: 7/5.3⁰ + 36
D: 7/1 + 4 × 9
A: 7/5.3 + 4×9
B: 7/0 + 4 ×9
C: 7/5.3⁰ + 36
D: 7/1 + 4 × 9
The correct answer is D: 7/1 + 4 × 9.
According to the Zero Power Rule, any nonzero number raised to the power of zero is equal to 1. In this case, (-5.3)⁰ = 1. Therefore, the expression 7/ (-5.3)⁰ can be simplified to 7/1.
The expression 7/1 + 4 × 9 is equivalent to 7 + 36, which simplifies to 43. Therefore, option D is the correct equivalent expression when applying the Zero Power Rule.
Options A, B, and C do not apply the Zero Power Rule correctly, as none of them simplify the expression correctly to 7/1.
According to the Zero Power Rule, any nonzero number raised to the power of zero is equal to 1. In this case, (-5.3)⁰ = 1. Therefore, the expression 7/ (-5.3)⁰ can be simplified to 7/1.
The expression 7/1 + 4 × 9 is equivalent to 7 + 36, which simplifies to 43. Therefore, option D is the correct equivalent expression when applying the Zero Power Rule.
Options A, B, and C do not apply the Zero Power Rule correctly, as none of them simplify the expression correctly to 7/1.
Which of the following is an equivalent expression to 1/2(9 -7⁰) + (-29)⁰?
A: 1/2(9 - 0) + 0
B: 1/2 (9-1) + 1
C: 1/2 (9 - 1) - 1
D: 1/2 (2) + 1
A: 1/2(9 - 0) + 0
B: 1/2 (9-1) + 1
C: 1/2 (9 - 1) - 1
D: 1/2 (2) + 1
The correct answer is A: 1/2(9 - 0) + 0.
By applying the Zero Power Rule, we know that any number (except 0) raised to the power of 0 is equal to 1. Therefore, (-7)⁰ = 1.
Simplifying the expression, we get:
1/2(9 - 7⁰) + (-29)⁰ = 1/2(9 - 1) + 1
= 1/2(8) + 1
= 4 + 1
= 5
Therefore, option A: 1/2(9 - 0) + 0 is the correct equivalent expression.
Options B, C, and D incorrectly apply the Zero Power Rule and do not simplify the expression correctly.
By applying the Zero Power Rule, we know that any number (except 0) raised to the power of 0 is equal to 1. Therefore, (-7)⁰ = 1.
Simplifying the expression, we get:
1/2(9 - 7⁰) + (-29)⁰ = 1/2(9 - 1) + 1
= 1/2(8) + 1
= 4 + 1
= 5
Therefore, option A: 1/2(9 - 0) + 0 is the correct equivalent expression.
Options B, C, and D incorrectly apply the Zero Power Rule and do not simplify the expression correctly.
Which of the following shows the correct process of solving -4 (3 +12⁰) + 15⁰ by generating an equivalent expression using the Zero Power Rule?
The correct process of solving -4 (3 + 12⁰) + 15⁰ by generating an equivalent expression using the Zero Power Rule is shown as follows:
-4 (3 + 12⁰) + 15⁰
Since any number (except 0) raised to the power of 0 is equal to 1, we can simplify 12⁰ to 1:
-4 (3 + 1) + 15⁰
Now, we can simplify the parentheses:
-4 (4) + 15⁰
Next, we can simplify the multiplication:
-16 + 15⁰
Finally, since any number (except 0) raised to the power of 0 is equal to 1, we can simplify 15⁰ to 1:
-16 + 1
Therefore, the correct process of solving -4 (3 + 12⁰) + 15⁰ by generating an equivalent expression using the Zero Power Rule is -16 + 1.
-4 (3 + 12⁰) + 15⁰
Since any number (except 0) raised to the power of 0 is equal to 1, we can simplify 12⁰ to 1:
-4 (3 + 1) + 15⁰
Now, we can simplify the parentheses:
-4 (4) + 15⁰
Next, we can simplify the multiplication:
-16 + 15⁰
Finally, since any number (except 0) raised to the power of 0 is equal to 1, we can simplify 15⁰ to 1:
-16 + 1
Therefore, the correct process of solving -4 (3 + 12⁰) + 15⁰ by generating an equivalent expression using the Zero Power Rule is -16 + 1.
Which of the following shows the correct process of solving -4 (3 +12⁰) + 15⁰ by generating an equivalent expression using the Zero Power Rule?
A: -4 (3 + 12⁰) + 15⁰ = -4 (15) +15 = -60 + 15 = -45
B: -4 (3+12⁰) + 15⁰ = -4 (3+1) + 1 = -4 × 4 + 1 = -16 +1 = -15
C: -4 (3+12⁰) + 15⁰ = -4 (3+1) +1 = -4 ×4 +1 = -4 × 5 = -20
D: -4 (3 +12⁰) + 15⁰ = -4 (15) + 1 = -60 +1 = -59
A: -4 (3 + 12⁰) + 15⁰ = -4 (15) +15 = -60 + 15 = -45
B: -4 (3+12⁰) + 15⁰ = -4 (3+1) + 1 = -4 × 4 + 1 = -16 +1 = -15
C: -4 (3+12⁰) + 15⁰ = -4 (3+1) +1 = -4 ×4 +1 = -4 × 5 = -20
D: -4 (3 +12⁰) + 15⁰ = -4 (15) + 1 = -60 +1 = -59
The correct process of solving -4 (3 +12⁰) + 15⁰ by generating an equivalent expression using the Zero Power Rule is shown in option A:
-4 (3 + 12⁰) + 15⁰ = -4 (15) + 15 = -60 + 15 = -45
Therefore, option A: -4 (3 + 12⁰) + 15⁰ = -4 (15) + 15 = -60 + 15 = -45 is the correct process of solving the expression using the Zero Power Rule.
Options B, C, and D do not apply the Zero Power Rule correctly and do not simplify the expression correctly.
-4 (3 + 12⁰) + 15⁰ = -4 (15) + 15 = -60 + 15 = -45
Therefore, option A: -4 (3 + 12⁰) + 15⁰ = -4 (15) + 15 = -60 + 15 = -45 is the correct process of solving the expression using the Zero Power Rule.
Options B, C, and D do not apply the Zero Power Rule correctly and do not simplify the expression correctly.
Don’t listen to bot I got a 1/5
1. (-2.97)^0***
2. I don’t wanna type it, it’s the one ending in 3.5
3. Listen to bot
4. 1/2(9-1)+1
5.the one ending in 15
100% trust me
2. I don’t wanna type it, it’s the one ending in 3.5
3. Listen to bot
4. 1/2(9-1)+1
5.the one ending in 15
100% trust me